Optical sensing of mechanical pressure based on diffusion measurement in polyacrylamide cell-like barometers. Issue 23 (5th June 2017) - Ingremeau, F.; Dolega, M. E.; Gallagher, J.; Wang, I.; Cappello, G.; Delon, A.
Abstract : Diffusion coefficient ( D ) of a tracer inside hydrogels decreases under compression due to the changes in volume fraction ( ϕ ). We used this phenomenon to measure tissue stress. Abstract : Diffusion and transport of small molecules within hydrogel networks are of high interest for biomedical and pharmaceutical research. Herein, using fluorescence correlation spectroscopy (FCS), we experimentally showed that the diffusion time in the hydrogel was directly related to the mechanical state (compression or swelling) and thus to the volume fraction of the gel. Following this observation, we developed cell-like barometers in the form of PAA microbeads, which when incorporated between cells and combined with a diffusion-based optical readout could serve as the first biosensors to measure the local pressure inside the growing biological tissues. To illustrate the potential of the present method, we used multicellular spheroids (MCS) as a tissue model, and it was observed that the growth-associated tissue stress was lower than 1 kPa, but significantly increased when an external compressive stress was applied.